2016
DOI: 10.1016/j.neurobiolaging.2016.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated anticorrelation between the default and dorsal attention networks with aging: evidence from task and rest

Abstract: Anticorrelation between the default and dorsal attention networks is a central feature of human functional brain organization. Hallmarks of aging include impaired default network modulation and declining medial temporal lobe (MTL) function. However, it remains unclear if this anticorrelation is preserved into older adulthood during task performance, or how this is related to the intrinsic architecture of the brain. We hypothesized that older adults would show reduced within- and increased between-network funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
171
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 210 publications
(207 citation statements)
references
References 81 publications
(155 reference statements)
34
171
2
Order By: Relevance
“…Similar patterns of network differentiation with age have been reported in a more circumscribed set of brain networks, including the default, dorsal attention and frontal parietal control networks both during task and at rest [122,123]. Specific changes include reduced anticorrelations between dorsal attention and default networks and increased network interactions across all three networks, consistent with a network dedifferentiation account.…”
Section: Changes In Functional Brain Networksupporting
confidence: 70%
See 1 more Smart Citation
“…Similar patterns of network differentiation with age have been reported in a more circumscribed set of brain networks, including the default, dorsal attention and frontal parietal control networks both during task and at rest [122,123]. Specific changes include reduced anticorrelations between dorsal attention and default networks and increased network interactions across all three networks, consistent with a network dedifferentiation account.…”
Section: Changes In Functional Brain Networksupporting
confidence: 70%
“…Age-related changes include reduced suppression [112,116,117] and decreased within-network connectivity during both task [110,113,118] and rest [108,109,119,120]. Recent evidence also suggests that the default network is more functionally connected to other brain networks in aging [113,114,[119][120][121][122] and this connectivity is poorly modulated by task context [96,97,[122][123][124].…”
Section: Changes In Functional Brain Networkmentioning
confidence: 99%
“…These age differences in associations were observed despite of a lack of group difference in the average DAN-DMN anticorrelation score, which has been reported in previous studies (e.g., Keller et al, 2015;Spreng et al, 2016). This lack of average group difference may possibly be related to the nature of the task used, as various task demands have been shown to influence the degree of the networks' anticorrelation (e.g., Leech, Kamourieh, Beckman, & Sharp, 2011).…”
Section: Discussionsupporting
confidence: 58%
“…It is important to note that both age groups showed a wide range of anticorrelation scores (younger adults: -.43 to .35; older adults: -.53 to .53 -see Figure 2), however unlike previous studies (e.g., Spreng, Stevens, Viviano, & Schacter, 2016), there was no significant group difference in the average anticorrelation score, t < 1.…”
Section: Fmri Resultsmentioning
confidence: 53%
“…Heretofore, several fcMRI studies have documented age-related reduced connectivity within large-scale intrinsic connectivity networks (ICNs) (Andrews-Hanna et al, 2007; Damoiseaux et al, 2008; Koch et al, 2010; Tomasi and Volkow, 2012; Ferreira and Busatto, 2013), and altered connectivity between ICNs has also been proposed (Onoda et al, 2012; Antonenko and Floel, 2014). However, this literature refers to only a few ICNs, lifespan trajectories of intra-network connectivity decline and differences between networks are not well characterized and results regarding inter-network connectivity changes are variable, with both increases (Meunier et al, 2009; Betzel et al, 2014; Chan et al, 2014; Geerligs et al, 2015; Grady et al, 2016; Spreng et al, 2016) and decreases (Meunier et al, 2009; Allen et al, 2011; Onoda et al, 2012) reported.…”
Section: Introductionmentioning
confidence: 99%